What factors influence innovation efficiency in integrating digitalization and low carbonization within the construction industry? A configuration analysis based on fsQCA. - Shiming Wang; Haifeng Xiong (PLoS ONE)
In the dual context of the digital age and the 'double carbon' objectives, enhancing the innovation efficiency of integrating digitalization and low carbonization in the construction industry has become an inevitable trend. This study utilizes the fuzzy set Qualitative Comparative Analysis (fsQCA) method, framed within the Technology-Organization-Environment (TOE) theoretical perspective. By analyzing data from 30 provinces, the research examines how technological, organizational, and environmental factors influence the innovation efficiency of integrating digitalization and low carbonization in the construction sector from a configurational standpoint. The findings reveal that, as a whole, there is a necessary condition for the potential absence of high innovation efficiency in this integration within the construction industry. Additionally, no singular necessary condition was identified that affects high innovation efficiency in the sector. The study identifies four equivalent configuration pathways to enhance innovation efficiency by integrating digitalization and low carbonization. These pathways suggest that provinces can select a trajectory more suitable for the synergistic advancement of "digitalization and low carbonization" in the construction sector based on local city conditions, ultimately achieving the "dual carbon" goal. The research findings support the "Porter hypothesis," highlighting the critical role of environmental regulation in improving the innovation efficiency of this integration within the construction industry.